Tumor Regression in Lymph Node Metastases of Esophageal Adenocarcinomas after Neoadjuvant Therapy - Marek Osecky; Dino Kröll; Marcus Feith; Daniel Reim; Bastian Dislich; Karen Becker; Rupert Langer (Gastrointestinal Disorders, 2020)
Tumor regression following neoadjuvant treatment can be observed in lymph node (LN) metastases similar to the primary tumor in esophageal adenocarcinomas (EAC). We evaluated the prognostic significance of tumor regression in LN metastases of locally advanced EAC of 239 patients treated with neoadjuvant radiochemotherapy (RCTX) or chemotherapy (CTX) followed by esophagectomy. We examined retrospectively the LN for histopathologic signs of regression, i.e., nodular fibrosis and acellular mucin. LN classification was performed according to two parameters: presence (−) or absence (+) of residual tumor and regression characteristics in the LN, resulting in four categories: LN−/REG−, LN−/REG+, LN+/REG+, LN+/REG−. In total, LN metastases with residual tumor were detectable in 117/239 (49%) cases. Regression in LN were observed in 85/239 cases (35.5%). The distribution of the LN/REG categories were as follows: 97 patients (40.6%) were LN−/REG−. A total of 25 patients (10.5%) were LN−/REG+. A total of 60 (25.1%) were LN+/REG+ and 57 (23.8%) LN+/REG−. The LN/Reg categorization had a significant prognostic value in univariate analysis (p < 0.001) and multivariate analysis (HR = 1.326; p = 0.002) with similar results for the subgroups of patients treated with RCTX or CTX. The prognosis of LN−/REG+ was worse than LN−/REG− but better than both LN+ categories, which was demonstrated in the Kaplan–Meier curves but did not reach statistical significance (p = 0.104 and p = 0.090, respectively). In contrast, there was no difference between LN+/REG+ and LN+/REG− (p = 0.802). In summary, regression in LN metastases of EAC can be observed in a significant number of patients after neoadjuvant therapy. Complete regression of former LN metastases in comparison to “true” negative LN seems to be of prognostic relevance but additional studies are needed to confirm this trend seen in our study.